Different Resting State EEG Features in Children from Switzerland and Saudi Arabia - Alahmadi, Nsreen; Evdokimov, Sergey A.; Kropotov, Yury (Juri); Müller, Andreas M.; Jäncke, Lutz (Frontiers in Human Neuroscience, 2016)
Background: Cultural neuroscience is an emerging research field concerned with studying the influences of different cultures on brain anatomy and function. In this study we examined whether different cultural or genetic influences might influence the resting state electroencephalogram (EEG) in young children (mean age 10 years) from Switzerland and Saudi Arabia. Methods: Resting state EEG recordings were obtained from relatively large groups of healthy children (95 healthy Swiss children and 102 Saudi Arabian children). These EEG data were analyzed using group independent component analyses and conventional analyses of spectral data, together with estimations of the underlying intracortical sources, using LORETA software. Results: We identified many similarities, but also some substantial differences with respect to the resting state EEG data. For Swiss children, we found stronger delta band power values in mesial frontal areas and stronger power values in 3 out of 4 frequency bands in occipital areas. For Saudi Arabian children, we uncovered stronger alpha band power over the sensorimotor cortex. The additionally measured theta/beta ratio was similar for Swiss and Saudi Arabian children. Conclusions: The different EEG resting state features identified, are discussed in the context of different cultural experiences and possible genetic influences. In addition, we emphasize the importance of using appropriate EEG databases when comparing resting state EEG features between groups. Keywords: intercultural neuroscience, EEG, resting state EEG, children, LORETA, group independent component analysis.